EDUKASI FLEBOTOMI PADA SISWA SMK INDO HEALTH SCHOOL PALEMBANG JURUSAN TEKNOLOGI LABORATORIUM MEDIS - Indah Sari (Khidmah, 2021)
A clinical laboratory is a health laboratory that carries out clinical specimen examination services to obtain information about individual health, especially to support efforts to diagnose disease, cure disease, and restore health. The results of laboratory tests are strongly influenced by the pre-analytical, analytical and post-analytic stages. The biggest error contribution in the laboratory, namely in the pre-analytic stage, occurred at 77.1%. One of the health services at the forefront of laboratory services is phlebotomy. Phlebotomy is one of the main reasons behind pre analytic errors. Currently medical laboratory technology experts pay less attention to pre-analytical processes in the laboratory such as the process of taking blood samples (phlebotomy) so it is necessary to socialize and educate about phlebotomy for students of SMK Indo Health School (IHS) majoring in medical laboratory technology which aims to increase knowledge and understanding students regarding the pre-analytic stage, especially in blood sampling (phlebotomy) so as to prevent errors in the post-analytic stage. Solutions that can answer the problems faced by medical laboratory technology experts, it is necessary to carry out socialization and education about phlebotomy, so as to increase the knowledge and understanding of students of SMK Indo Health School (IHS) majoring in medical laboratory technology, totaling 30 participants at the pre-analytic stage, especially in taking blood samples (phlebotomy) as well as the selection of poster education media aims to explain about phlebotomy, demonstrate the stages of phlebotomy and the importance of a good phlebotomy stage in laboratory examination.